Outcome in a series of 1135 twin pregnancies: does the type of conception play a role?AJOG Global Reports at a Glance - Pilar Prats, MD, PhD; Janire Zarragoitia, MD; Maria Ángeles Rodríguez, MD, PhD; Ignacio Rodriguez, Msc; Francisca Martinez, MD, PhD; Alberto Rodríguez-Melcon, MD; Bernat Serra, MD (AJOG Global Reports, 2022)
BACKGROUND: The rate of twin pregnancies conceived via assisted reproductive technology has increased markedly in recent years. The elevated number of multiple pregnancies is the most serious and frequent complication of assisted reproductive technology. Twin pregnancies are associated with higher rates of obstetrical complications, preterm delivery, and perinatal morbidity and mortality than singleton pregnancies. OBJECTIVE: This study aimed to investigate the association between the mode of conception and obstetrical and perinatal outcomes in twin pregnancies, adjusting for parity, age, and chorionicity. STUDY DESIGN: This was a retrospective cohort study of 1135 twin pregnancies between May 2006 and April 2021. All spontaneous (n=369) and assisted reproductive technology–conceived (n=766) twin pregnancies with antenatal care and delivery in the Universitari Quiron-Dexeus Hospital, Barcelona, Spain, a tertiary obstetrical care center, were studied according to chorionicity. RESULTS: The mean maternal age was higher among assisted reproductive technology twin pregnancies than among naturally conceived ones, and there were also less parous women in the assisted reproductive technology twin group. The global survival rates in both groups of twins were practically identical, namely 744 of 766 (97.1%) assisted reproductive technology twins and 357 of 369 (96.8%) spontaneously conceived twins. Patients with dichorionic assisted reproductive technology twins had a higher incidence of gestational diabetes (relative risk, 1.69; 95% confidence interval, 1.10–2.59) and gestational hypertension or preeclampsia (relative risk, 2.75; 95% confidence interval, 1.60–4.729). Monochorionic diamniotic assisted reproductive technology twins had a higher risk for gestational diabetes (relative risk, 4.12; 95% confidence interval, 1.35–12.56). We analyzed the gestational age at delivery, onset of labor, type of delivery, rate of preterm births, weight discordance, rate of small for gestational age neonates and intrauterine growth restriction, and admission to the neonatal intensive care unit. We could not find any statistical differences between monochorionic diamniotic assisted reproductive technology twins and spontaneously conceived twins. Among dichorionic twins, those conceived by assisted reproductive technology had an earlier gestational age at delivery (36.3±2.29 vs 36.6±2; P<.05) and we found statistical differences in the onset of labor with more cesarean deliveries (relative risk, 1.27; 95% confidence interval, 1.06–1.51). When adjusting for cofounding factors (maternal age, parity, chorionicity), the type of conception remained an independent risk factor for gestational hypertension and preeclampsia but not for gestational diabetes or cesarean delivery. CONCLUSION: Pregnancy outcomes are comparable between assisted reproductive technology and spontaneously conceived twins, and when adjusted for confounding factors, only the risk for gestational hypertension and preeclampsia remained increased in the assisted reproductive technology group.